2013
DOI: 10.2174/13894501113146660213
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vectors: A Powerful Tool to Target Astrocytes In Vivo

Abstract: The morphological and functional diversity of astrocytes, and their essential contribution in physiological and pathological conditions, are starting to emerge. However, experimental systems to investigate neuron-glia interactions and develop innovative approaches for the treatment of central nervous system (CNS) disorders are still very limited. Fluorescent reporter genes have been used to visualize populations of astrocytes and produce an atlas of gene expression in the brain. Knock-down or knock-out of astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…Lentiviral vectors (LV) were found to have pseudotype-dependent neuron and glia tropism. Based on such vectors, it is possible to target astrocytes in vivo through modifying LV pseudotype, integrating cell-specific promoters, and using miRNA post-transcriptional regulatory elements [135-137]. However, more studies are needed to take the heterogeneity of astrocytes into consideration, especially when astrocytes are in pathological conditions.…”
Section: 3 Targeting Astrocytesmentioning
confidence: 99%
“…Lentiviral vectors (LV) were found to have pseudotype-dependent neuron and glia tropism. Based on such vectors, it is possible to target astrocytes in vivo through modifying LV pseudotype, integrating cell-specific promoters, and using miRNA post-transcriptional regulatory elements [135-137]. However, more studies are needed to take the heterogeneity of astrocytes into consideration, especially when astrocytes are in pathological conditions.…”
Section: 3 Targeting Astrocytesmentioning
confidence: 99%
“…This is in contrast to a number of other studies using VSV-G-pseudotyped HIV-based lentiviral vectors in murine or rat brain, in which a clear prevalence for transduced neurons was observed (e.g., Naldini et al 1996a ; Blömer et al 1997 ; Bensadoun et al 2000 ). However, it has been demonstrated that beside the observed transduction specificity, the choice of the promotor sequence can invoke exclusive expression of the gene of interest in either glial cells or (specific) neurons (Jakobsson et al 2003 ; Delzor et al 2013 ; Schulze et al 2015 ). To avoid this promoter-driven restriction of EGFP expression, we used the strong, ubiquitous SFFV promoter with described activity in neuronal cells (Bender et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 ), which would be in agreement with the EGFP expression data of HIV-1 vectors published previously (Baekelandt et al 2002 ). Diversity in the expression levels might be accounted to differences in promoter activity between these two cell types and/or to disparity in transcription and translation rate among these cells (Stoykova et al 1985 ; Delzor et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, delivered transgene with the binding site for miR-122 can be easily silenced in hepatocytes because it has specificity for liver tissues (133). This strategy has been widely used to restrict transgene expression through a lentiviral vector in astroglial cells (134,135) (134,136).…”
Section: Microrna In Neurological Disordersmentioning
confidence: 99%